Photon upconversion tuning through energy migration in lanthanides sensitized nanoparticles - Xingwen Cheng; Jiangshan Luo; Federico Rosei (Nano Materials Science)
Lanthanide-sensitized upconverting nanoparticles (UCNPs) are widely studied because of their unusual optical characteristics, such as large antenna-generated anti-Stokes shifts, high photostability, and narrow emission bandwidths, which can be harnessed for a variety of applications including bioimaging, sensing, information security and high-level anticounterfeiting. The diverse requirements of these applications typically require precise control over upconversion luminescence (UCL). Recently, the concept of energy migration upconversion has emerged as an effective approach to modulate UCL for various lanthanide ions. Moreover, it provides valuable insights into the fundamental comprehension of energy transfer mechanisms on the nanoscale, thereby contributing to the design of efficient lanthanide-sensitized UCNPs and their practical applications. Here we present a comprehensive overview of the latest developments in energy migration upconversion in lanthanide-sensitized nanoparticles for photon upconversion tuning, encompassing design strategies, mechanistic investigations and applications. Additionally, some future prospects in the field of energy migration upconversion are also discussed.